Cancer care for transgender and gender‐diverse people: Practical, literature‐driven recommendations from the Multinational Association of Supportive Care in Cancer - Elizabeth J. Cathcart‐Rake; Alexandre Chan; Alvaro Menendez; Denise Markstrom; Carla Schnitzlein; Yee Won Chong; Don S. Dizon (CA: A Cancer Journal for Clinicians, 2025)
Abstract In the United States, over 2 million individuals openly identify with a gender that differs from their sex assigned at birth. A cancer diagnosis is physically and psychologically taxing—and, in some, traumatic. However, for transgender and gender‐diverse (TGD) people, many of whom have experienced discrimination in myriad health care settings, the challenges may be even greater. These recommendations focus on how best to deliver quality cancer care to transgender men (individuals who identify as men but were assigned female sex at birth), transgender women (individuals who identify as women but were assigned male sex at birth), and people who identify somewhere beyond this gender spectrum as nonbinary or using other terms, based on the available, albeit sparse, literature. This review broaches: (1) the epidemiology of cancer in TGD individuals, including the incidence of cancer and cancer‐related mortality; (2) cancer center practices that are welcoming and affirming to TGD patients; (3) the need for awareness and intentionality in the spaces of diagnosis and treatment for cancer; (4) the inevitable conclusion that gender differences exist but much more needs to be learned about the impact of gender‐affirming therapy, consisting of gender‐affirming surgeries and gender‐affirming hormone therapy, on cancer therapy; and (5) the efficacy and perceived safety of antineoplastic therapy and gender‐affirming hormone therapy.